Southern Fried : Going Whole Hog in a State of Wonder - Nelson, Rex (Book collections on Project MUSE., 2016)
"For decades, journalist Rex Nelson has been traveling Arkansas. In this collection of columns from the Arkansas Democrat-Gazette he brings to life the personalities, communities, festivals, and tourist attractions that make Arkansas unique"--